2002
DOI: 10.2464/jilm.52.179
|View full text |Cite
|
Sign up to set email alerts
|

Resistometric investigation on effect of Cu addition on 473 K aging behavior of Al-1%Mg2Si alloys.

Abstract: ABE , Shin-ya KOMATSU  Masahiko IKEDA and Takeo SAKURAI   Al 1Mg 2 Si 0,  0.17,  0.43,  0.72Cu alloys were solution treated for 3.6 ks at 848 K, water quenched and aged at 473 K. Behavior of added Cu during these heat treatments and eŠect of the Cu on age-hardening were investigated by resistometry and tensile test with assist of transmission electron microscopy. The resistivity in as water quenched state well coincides with the value calculated from 0.023 massFe, the equilibrium solubility at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…18) This precipitate may cause this behavior during quenching, because the added Cu for an Al-1.0 mass% Mg 2 Si alloy can be obtained as 0.17-0.72 mass% at 848 K, which is the same temperature of the present solution heat treatment. 19) According to Wolverton's result by a first-principles total energy method, the fcc-based formation enthalpies with special quasi-random structures, ÁH fcc SQS , for Cu-Mg and MgSi have been calculated as À2:6 and À16: 4. 20) As the value of Cu-Mg is smaller than that of Mg-Si, formation of Cu-Mg clusters as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…18) This precipitate may cause this behavior during quenching, because the added Cu for an Al-1.0 mass% Mg 2 Si alloy can be obtained as 0.17-0.72 mass% at 848 K, which is the same temperature of the present solution heat treatment. 19) According to Wolverton's result by a first-principles total energy method, the fcc-based formation enthalpies with special quasi-random structures, ÁH fcc SQS , for Cu-Mg and MgSi have been calculated as À2:6 and À16: 4. 20) As the value of Cu-Mg is smaller than that of Mg-Si, formation of Cu-Mg clusters as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The water transparency (WT) in the MC simulation is defined using absorption and scattering coefficients as a function of wavelength (see [10] for details). The dominant contribution to the variation of the WT is a variation in the absorption length.…”
Section: Detector Performancementioning
confidence: 99%
“…Due to the precise control of the input water temperature, the convection inside the tank is minimized everywhere but the bottom, below z = −11 m. Due to a small amount of convection in the bottom of the tank and a constant rising temperature above, the absorption coefficient is modeled as a constant below z = −11 m and with a linear function above this height. This "top-bottom" asymmetry of the WT is determined by studying the distribution of hits coming from a Ni-Cf gamma-ray source (see [10]) in the "top", "bottom" and "barrel" regions of the detector. It is found that the hit rate of the top region of the detector is 3 ∼ 5% lower than that of the bottom region.…”
Section: Detector Performancementioning
confidence: 99%
See 1 more Smart Citation
“…reconstructing emission angles of individual Cherenkov photons radiated by charged particles passing through liquid and gas radiator systems of the SLD Cherenkov Ring Imaging Detector (CRID) [2]. In each momentum bin, identified π, K, and p were counted, and these were unfolded using the inverse of an identification efficiency matrix [3], and corrected for track reconstruction efficiency.…”
Section: Introductionmentioning
confidence: 99%